Animal Labourers and the Law in Colonial India. (July 2019) - Chhabra, Heeral
This article is a tentative effort to highlight the symbiotic but systematically underrated position of animals in labour history. It argues for an expansion of human-centric definitions of labour to include non-human animals in this domain. The discussion focuses in later parts on colonial rule in India to examine debates about three colonial legislative enactments dealing with animals as labouring bodies in various capacities. Predictably, this colonial discourse and intervention remains human-centric, too. Yet, closer reading of such historical evidence also indicates exciting scope for developing various aspects of the 'animal question' in relation to labour history and South Asian studies.